(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Gonadal dysgenesis is a rare cause of primary amenorrhoea ,which is a relatively common problem among teenage girls.Primary amenorrhoea occurs in patient with gonadal dysgenesis because of absence or limited ovarian function due to inappropriate development.Streak gonads are unable to produce estrogens and/or androgens,resulting in minimal to no development of secondary sexual characteristics.Adrenal androgens may induce production of pubic hair,but patient will have minimal breast development.These patients may have a family history of infertility, short stature,sensorineural deafness,ataxia,mild mental retardation or gonadoblastoma. Here two cases of primary amenorrhoea due to pure gonadal dysgenesis are presented. 1 st one was a 18yr old girl whose mother consulted with a gynaecologist at the age of 16yr because of her worries about absence of menarche of her daughter and secondone was a 14yr old girl whose mother consulted with a gynaecologist at the age of 16yr because of absence of secondary sexual characteristics as well as menarche of her daughter. In both cases, blood test showed very high levels of follicle stimulating hormone (FSH) & luteinizing hormone (LH), low levels of oestradiol& very low level of AMH. USG findings of both cases showed a bit hypoplastic uterus and volume of ovaries were smaller than normal. A diagnostic laparoscopy with biopsy of both gonads of one case was performed.Another case did not give consent for laparoscopy.Hormonal replacement therapy was applied on them for establishment of normal menstruation and menstruation was established in both cases. An early diagnosis is extremely important to prevent long term consequences of Gonadal dysgenesis. J Bangladesh Coll Phys Surg 2018; 36(4): 170-174